Analisis Penggunaan Google Classroom Pada Masa Pandemi Covid – 19 Terhadap Efektivitas Pembelajaran Mahasiswa - Wahyuni, Hari; Erwantiningsih, Erni; Pudyaningsih, Ratna (Jurnal Pendidikan Ekonomi Undiksha, 2021)
The Covid-19 pandemic has caused various sectors to experience obstacles, one of the sectors that has been greatly affected is the world of education. The government implements policies related to education so that students learn from home by utilizing technology facilities. One of them is the Management Study Program, Faculty of Economics, Merdeka University, Pasuruan, which must change the conventional learning system with online learning. Online learning carried out in the Management Study Program by utilizing the Google Classroom application. So the purpose of this study is to analyze the use of Google Classroom during the Covid-19 pandemic on the effectiveness of student learning. Based on the research results, perceived usefulness has a direct effect on the use of Google Classrooms, perceptions of comfort and service quality also directly affect the use of Google Classroom, while user interest has no effect on the use of Google Classroom. The indirect effect of perceived usefulness on the effectiveness of student learning through the use of Google Classroom is not supported, while perceptions of convenience, user interest and service quality on the effectiveness of student learning through the use of Google Classroom are supported.